Efforts to Improve the Performance of Rapid Response Patrols by the Samapta Unit in Preventing Motorcycle Theft in the Jurisdiction of Surabaya Police Headquarters - Helena Fiorentina (Akademi Kepolisian Republik Indonesia, 2023)
The city of Surabaya is one of the largest metropolitan cities in East Java Province, and is one of the most populous cities. As one of the largest and most populous Metropolitan Cities, Surabaya has a high crime rate. Several forms of high criminality in Surabaya are theft, cheating and stealing. Motor vehicle theft (curanmor) is one of the highest numbers among the three with the latest data in 2023 there were 544 thefts. This research aims to examine the implementation and performance efforts of Satsamapta Quick Response Patrols to prevent criminal acts of theft in the jurisdiction of the Surabaya Police. This research method is qualitative research using interview instruments, observation and document study. Several things show that efforts to implement Respatti patrols at the Surabaya Police can still be improved. This research concludes that communication with the Head of Samapta is needed to improve several things such as; (1) Standard stages, (2) Random inspections or inspections, (3) More sophisticated technology, (4) Further attention to the results of audits related to the discovery of theft.